Advances in fluorescent carbon dots for biomedical applications. Issue 1 (1st January 2020) - Koutsogiannis, Panagiotis; Thomou, Eleni; Stamatis, Haralambos; Gournis, Dimitrios; Rudolf, Petra
ABSTRACT: Carbon Dots are an emerging class of carbon-based nanoparticles, which since their discovery have attracted tremendous attention because of their exceptional fluorescent, chemical and mechanical properties as well as high photostability and biocompatibility. This unique combination of outstanding characteristics, together with the ease with which they can be synthesized, qualify carbon dots as highly promising materials for applications in electronics and biology, in particular, for biosensing, bioimaging, biotherapy and drug delivery. In this review, we present some of the most recent applications of carbon dots in biology and medicine, concentrating on their fluorescence properties, biocompatibility and efficiency; we also discuss how improvements could prompt their use in human studies. We illustrate how carbon dots, prepared through several facile and cost-effective methods by either the bottom-up or the top-down route, can be used for imaging cells and bacteria and as sensing probes of metal cations. Moreover, we explain how their astonishing versatility has given rise to new biotherapy methods especially in the field of cancer theranostics. GRAPHICAL ABSTRACT: